Genomic analyses of multidrug-resistant Salmonella Indiana, Typhimurium, and Enteritidis isolates using MinION and MiSeq sequencing technologies - Chen, Zhao; Kuang, Dai; Xu, Xuebin; González-Escalona, Narjol; Erickson, David L.; Brown, Eric; Meng, Jianghong (PloS one, 2020)
We sequenced 25 isolates of phenotypically multidrug-resistant Salmonella Indiana (n = 11), Typhimurium (n = 8), and Enteritidis (n = 6) using both MinION long-read [SQK-LSK109 and flow cell (R9.4.1)] and MiSeq short-read (Nextera XT and MiSeq Reagent Kit v2) sequencing technologies to determine the advantages of each approach in terms of the characteristics of genome structure, antimicrobial resistance (AMR), virulence potential, whole-genome phylogeny, and pan-genome. The MinION reads were base-called in real-time using MinKnow 3.4.8 integrated with Guppy 3.0.7. The long-read-only assembly, Illumina-only assembly, and hybrid assembly pipelines of Unicycler 0.4.8 were used to generate the MinION, MiSeq, and hybrid assemblies, respectively. The MinION assemblies were highly contiguous compared to the MiSeq assemblies but lacked accuracy, a deficiency that was mitigated by adding the MiSeq short reads through the Unicycler hybrid assembly which corrected erroneous single nucleotide polymorphisms (SNPs). The MinION assemblies provided similar predictions of AMR and virulence potential compared to the MiSeq and hybrid assemblies, although they produced more total false negatives of AMR genotypes, primarily due to failure in identifying tetracycline resistance genes in 11 of the 19 MinION assemblies of tetracycline-resistant isolates. The MinION assemblies displayed a large genetic distance from their corresponding MiSeq and hybrid assemblies on the whole-genome phylogenetic tree, indicating that the lower read accuracy of MinION sequencing caused incorrect clustering. The pan-genome of the MinION assemblies contained significantly more accessory genes and less core genes compared to the MiSeq and hybrid assemblies, suggesting that although these assemblies were more contiguous, their sequencing errors reduced accurate genome annotations. Our research demonstrates that MinION sequencing by itself provides an efficient assessment of the genome structure, antimicrobial resistance, and virulence potential of Salmonella; however, it is not sufficient for whole-genome phylogenetic and pan-genome analyses. MinION in combination with MiSeq facilitated the most accurate genomic analyses.